The role of the police in tackling cyber crime on social media - Prayitno, Ahmad Hadi; Ridwan, Masroor; Sudarmadji, Aji (Jurnal Info Sains : Informatika dan Sains, 2024)
The development of information and communication technology causes world relations to become borderless and causes significant social, economic, and cultural changes to take place so quickly. On the one hand, technological advances have a positive impact, but also have a negative impact, with the emergence of various types of Cybercrime. Cybercrime or cybercrime is regulated in Law Number 19 of 2016 amending Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), especially in Articles 27 to 30 regarding prohibited acts, then a firm and clear attitude that cybercrime is a criminal act prohibited by law and every perpetrator will be dealt with according to applicable law. The purpose to be achieved from this study is to find out the role of the police in tackling Cybercrime on social media and what obstacles are faced by the police in tackling Cybercrime on social media and how to solve it. Primary Data is obtained through field studies (Fleld Research), while Secondary Data is obtained through literature studies (Library Research) with a series of documentation studies. The analytical method used in this study is empirical juridical. The results of this study show that law enforcement actions and efforts regarding the handling of Cybercrime are in the form of pre-emptive actions, preventive actions and repressive actions. In addition, internal constraints begin with weak government and police supervision, evidence in Cybercrime crimes is easily changed, deleted or hidden by criminals, there are rarely witnesses in Cybercrime cases and unclear jurisdiction determination. In addition, external constraints include law enforcement factors, facilities, community and environment, and cultural factors.